Standar Internasional Hak-Hak Dasar Buruh Penyandang Disabilitas dan Implementasinya dalam Hukum Perburuhan Nasional di Indonesia - Firmansyah Maulana; Alifia Berli Sukmayana; Awaludin Rohim S; Benny Nurcahyo; Ega Amalia Sani; Wahidyah Rahma Natsiriyat; Sandra Bagus N (CV Rewang Rencang, 2020)
The right to work is an inseparable human right because every human being and everyone has the right to participate in, contribute and enjoy economic, social, cultural and political development, where all fundamental human rights and freedoms can be fully realized, as stated in the 1986 Un Declaration on the Right to Development. This provision also overshadows the interests of the Disabled. People with disabilities in Indonesia until now are still very difficult in finding a job and carrying out work. In this paper, the author seeks to analyze the employment standards for people with disabilities internationally in Indonesia's positive law and explain the conditions of application and supervision based on the phenomena that occur.